Magnesium Alginate as an Electrolyte for Magnesium Batteries - Markus C. Kwakernaak; Lindah K. Kiriinya; Walter J. Legerstee; Winok M. J. Berghmans; Caspar G. T. Hofman; Erik M. Kelder (Batteries)
We present magnesium alginate as an aqueous polymer electrolyte for use in magnesium batteries. Alginates are polysaccharides extracted from algae, which form hydrogel materials upon interaction with divalent and trivalent cations. They are renewable, non-toxic, biocompatible materials that are widely used in the food and pharmaceutical industries. Mg2+ is weakly bound to an alginate polymer, which results in a hydrogel-like material that contains mobile magnesium ions. We propose that this is the ideal situation for an electrolyte that behaves in a similar way as a ‘water-in-salt’ system. Magnesium alginate was successfully synthesized and characterized by FTIR, XRD, and PDF. Ionic conductivity was measured with EIS measurements; a 2 wt% magnesium electrolyte shows a conductivity of 1.8 mS/cm. During conductivity experiments, we noticed the formation of a black layer on magnesium electrodes, which can improve the ionic conductivity between the electrodes. We carefully characterized this layer with XPS and saw that it mainly consists of alginate derivatives.